Effective treatment with mitotane for a canine case of Ectopic Cushing's syndrome-related pheochromocytoma. - Konatsu Miura; Hiroshi Sunahara; Yusuke Sakai (Open Veterinary Journal, 2022)
In humans, ectopic Cushing's syndrome (ECS) is characterized by hypercortisolemia, which is caused by small lung carcinoma, bronchial carcinoids, and pheochromocytoma. In dogs, only a few cases of ECS associated with pheochromocytoma has been reported to date. Herein, we describe a canine case of malignant pheochromocytoma that presumed to be the cause of ECS. An 11-year-old, castrated, male Toy Poodle with hypercortisolemia was diagnosed as adrenal tumor and treated with mitotane. Although repeated adrenocorticotropic hormone stimulation tests revealed improvement of the dog's condition by mitotane treatment, its condition started declining from 197 days post-diagnosis, and he died on day 280. The necropsy revealed the adrenal tumor was pheochromocytoma, not adrenocortical tumor. However, because of no pathological change in pituitary gland and the other adrenal gland, the pheochromocytoma was presumed to be the cause of ECS. This is the first report that describe the effectiveness of mitotane against presumed ECS-related pheochromocytoma. [Open Vet J 2022; 12(5.000): 762-767]